Strategi Guru Fikih Dalam Mengembangkan Kompetensi Kepribadian di Madrasah Aliyah Al-Ikhsan Beji Kedungbanteng - Nurfuadi Nurfuadi (Departement of Mathematics Education, 2023)
Good learning is in accordance with the characteristics of students and optimal use of the learning environment. The purpose of this paper is to describe and analyze the strategies of fiqh teachers in developing personality competencies at Madrasah Aliyah Al-Ikhsan Beji Kedungbanteng. This research is a qualitative research with the results of the research that so far the fiqh subject has only taken part once because there was another fiqh teacher who represented it while the Aqidah ahlak subject who took part in the MGMP was a representative of another teacher. The purpose of the MGMP activities is to improve the quality/quality of education, because one of the components in educational institutions is the teacher, a teacher must be able to improve human resources through various program activities that support the quality of education, one of which is as mentioned above, namely participating in the Subject Teacher Consultation activities ( MGMP). By participating in the MGMP, you will increase your insight skills in carrying out your duties and role as a teacher